Chronic Non-infectious Osteomyelitis Mimicking Scurvy as the Presenting Sign of Crohn's Disease: Case Report - Alexa Goldfarb; Stefan Breitling; Owen Amadasun; Bridget Kiernan; Gabrielle Gold-von Simson; Selin T. Sagalowsky (Frontiers Media S.A., 2022)
Chronic non-infectious osteomyelitis (CNO) is a rare, inflammatory process associated with pediatric inflammatory bowel disease (IBD). Signs and symptoms of CNO parallel scurvy, a nutritional deficiency that can affect children with autism spectrum disorder (ASD). This is the first report of a child initially thought to have scurvy, then subsequently diagnosed with CNO as the presenting manifestation of Crohn's disease. This case enhances the literature elucidating extra-intestinal manifestations of IBD and pediatric nutritional deficiencies.